THE USE OF GAMES IN TEACHING A FOREIGN LANGUAGE AT A UNIVERSITY (Academia Science Repository, 2023)
The present article explores the potentiality of incorporating word games as an effective pedagogical tool for instructing a second language at an institution of higher learning. This discourse serves to provide an overview of the principal classifications of games, with particular emphasis on lexical-based gaming. This article presents a comprehensive discourse on the conditions that facilitate the efficient utilization of word games in foreign language instruction. Additionally, the paper furnishes illustrations of game-based strategies appropriate for various phases of students' learning.